2012
DOI: 10.1155/2012/843134
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Immunization Scheme for Spouses of Individuals Estabilished as Hepatitis B Carriers during Premarital Tests

Abstract: Background. The aim of this study was to monitor the cases identified as hepatitis B carriers during premarital tests, to vaccinate their prospective spouses with a rapid vaccination scheme, and to compare the anti-HBs responses with the traditional vaccination scheme. Methods. Blood samples of 1250 couple spouses were tested for HBsAg and anti-HBs. HBsAg positive cases' fiancées which were found HBV negative were administered a rapid three-dose vaccination scheme on days 0, 7, and 21. Forty controls with simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…In the current study, the high HBsAg prevalence of the participants (12.56%) suggested that married couples could be categorised into a high-epidemic group, and this was concordant with previous findings from the Pearl River Delta in 2016, in which the HBsAg prevalence was 12.71% among residents aged 23–59 years 5. However, when compared with the couples reported in other studies, the HBsAg prevalence in this study was much higher than that of rural couples in China (4.80%~6.07%) and married couples in other countries (1.7%~10.9%) 12–14 17–22. All of these implied the relatively high HBV burden of this population in Guangdong, which presents a significant public health threat and requires urgent interventions.…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, the high HBsAg prevalence of the participants (12.56%) suggested that married couples could be categorised into a high-epidemic group, and this was concordant with previous findings from the Pearl River Delta in 2016, in which the HBsAg prevalence was 12.71% among residents aged 23–59 years 5. However, when compared with the couples reported in other studies, the HBsAg prevalence in this study was much higher than that of rural couples in China (4.80%~6.07%) and married couples in other countries (1.7%~10.9%) 12–14 17–22. All of these implied the relatively high HBV burden of this population in Guangdong, which presents a significant public health threat and requires urgent interventions.…”
Section: Discussionsupporting
confidence: 89%
“…Ten more were subsequently excluded because they were irrelevant to the current research question. Specifically, 5 studies addressed the prevalence and management of hepatitis antigen positivity in a specific population,11-15 2 measured incidence trends or population perception of hepatitis B and C before any hepatitis PSP had been established,16,17 2 targeted diseases other than hepatitis,18,19 and one assessed physicians’ attitudes toward general HCV screening 20. One further study was excluded because it mainly discussed risk factors for transmission in the community and not screening for the viruses 21.…”
Section: Methodsmentioning
confidence: 99%